PERAN SUBSEKTOR PETERNAKAN TERHADAP SEKTOR PERTANIAN PADA PEREKONOMIAN WILAYAH PROVINSI LAMPUNG - Rino Hadiwijaya Puradireja; Achmad Firman (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
This study aims to determine the superior sub-sectors in the agricultural sector that can be developed in Lampung Province. This study uses secondary data obtained from the National Statistics Agency and the Province of Lampung. The analysis method used in this calculation consists of the Location Question (LQ), Shift Share (SS) and Klassen Typology. The results of this study indicate that the sub-sectors of food crops, livestock, agricultural services and hunting, and fisheries have a value of LQ > 1. It is the agricultural sub-sector that contributes greatly to the PDRB of Lampung Province. Those with a positive Shift Share (SS) value are the sub-sector of food crops, agricultural services and hunting, and fisheries. Based on the two LQ and SS analyzes, the classification typology value can be calculated which shows that the superior agricultural sub-sectors are the food crops, agricultural and hunting services, and fisheries sub-sectors.